Analysis methods for modeling of monolithic reinforced concrete foundations of houses increased storeys - Поляков, А.П. (Proceedings of National Aviation University (archive), 2009)
Numeral experiments in which the values of cuttings efforts were compared in at the supporting area of piles and colons in MPR with the change of step of piles are conducted. Two models were utilized: in the first the monolithic flag of grillage was designed as a flat element; in the second as spatial.